X‐ray acoustic computed tomography with pulsed x‐ray beam from a medical linear accelerator. Issue 1 (18th December 2012) - Xiang, Liangzhong; Han, Bin; Carpenter, Colin; Pratx, Guillem; Kuang, Yu; Xing, Lei
Abstract : Purpose: : The feasibility of medical imaging using a medical linear accelerator to generate acoustic waves is investigated. This modality, x‐ray acoustic computed tomography (XACT), has the potential to enable deeper tissue penetration in tissue than photoacoustic tomography via laser excitation. Methods: : Short pulsed ( μ s‐range) 10 MV x‐ray beams with dose‐rate of approximately 30 Gy/min were generated from a medical linear accelerator. The acoustic signals were collected with an ultrasound transducer (500 KHz central frequency) positioned around an object. The transducer, driven by a computer‐controlled step motor to scan around the object, detected the resulting acoustic signals in the imaging plane at each scanning position. A pulse preamplifier, with a bandwidth of 20 KHz–2 MHz at −3 dB, and switchable gains of 40 and 60 dB, received the signals from the transducer and delivered the amplified signals to a secondary amplifier. The secondary amplifier had bandwidth of 20 KHz–30 MHz at −3 dB, and a gain range of 10–60 dB. Signals were recorded and averaged 128 times by an oscilloscope. A sampling rate of 100 MHz was used to record 2500 data points at each view angle. One set of data incorporated 200 positions as the receiver moved 360°. The x‐ray generated acoustic image was then reconstructed with the filtered back projection algorithm. Results: : The x‐ray generated acoustic signals were detected from a lead rod embedded in a chicken breast tissue. The authors found that the acoustic signal was proportional to the x‐ray dose deposition, with a correlation of 0.998. The two‐dimensional XACT images of the lead rod embedded in chicken breast tissue were found to be in good agreement with the shape of the object. Conclusions: : The first x‐ray acoustic computed tomography image is presented. The new modality may be useful for a number of applications, such as providing the location of a fiducial, or monitoring x‐ray dose distribution during radiation therapy. Although much work is needed to improve the image quality of XACT and to explore its performance in other irradiation energies, the benefits of this modality, as highlighted in this work, encourage further study.